Exploring of Tax Compliance: Tax Practitioners Interpretation - Syamsudin; Siti Haerani; R.A. Damayanti; Sanusi Fattah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to find the meaning of tax compliance from the point of view of tax practitioners. The research uses qualitative research with a phenomenological methodology, and informants are taken from tax consultants with fifteen years of experience, and They are partners. The research results on the meaning of tax compliance consist of three: compliance is a risk mitigation. Compliance is obeying the law and obedience. The results of this study have the consequence that compliance does not apply to taxpayers only but also to tax authorities who enforce tax rules, judges who decide tax disputes, and tax consultants themselves